The Impact of Magnetic Materials in Renewable Energy-Related Technologies in the 21st Century Industrial Revolution: The Case of South Africa - Wallace Matizamhuka (Advances in Materials Science and Engineering)
Magnetic materials specifically permanent magnets are critical for the efficient performance of many renewable energy technologies. The increased reliance on renewable energy sources has accelerated research in energy-related technologies the world over. The use of rare-earth (RE) metals in permanent magnets continues to be a source of greater concern owing to the limited RE supply coupled with dwindling reserves on the globe. This review focuses on how this has impacted on the state-of-the-art magnetic materials that continue to play a pivotal role in driving renewable energy technologies. Magnetic materials are perceived as key in driving the 21st century industrial revolution, and the participation of South Africa in this energy paradigm is critical in driving a new industrial revolution within the African continent. A number of opportunities are highlighted, and clarity is given on the several ubiquitous misconceptions and the risks on the heavy reliance on a single source for RE magnetic materials.